Chiral diphosphites derived from (1R, 2R)-trans-1, 2-cyclohexanediol: a new class of ligands for asymmetric hydrogenations. Issue 24 (31st December 2015) - Pang, Zeng-bo; Li, Hai-feng; Tian, Mi; Wang, Lai-lai
Graphical abstract: Abstract: A series of novel chiral diphosphite ligands was easily prepared in a few steps from commercial (1 R, 2 R )- trans -1, 2-cyclohexanediol as the chiral source, and successfully employed in the Rh-catalyzed asymmetric hydrogenation of α, β-unsaturated carboxylic acid derivatives and enamides with up to 99% ee for dimethyl itaconate and enamides and with up to 94% ee for α-dehydroamino acid esters. The stereochemically matched combination of (1 R, 2 R )- trans -1, 2-cyclohexanediol backbone and ( S )-binaphthyl in the ligand (1 R, 2 R )-bis[( S )-1, 1′-binaphthyl-2, 2′-diyl]phosphitecyclohexanediol, was essential for inducing high enantioselectivity. Moreover, the sense of enantiodiscrimination of the products was mainly determined by the configuration of the binaphthyl moieties. Abstract : (1 R, 2 R )-Bis[( R )-1, 1′-binaphthyl-2, 2′-diyl]phosphitecyclohexanediol: C46 H34 O6 P2 [ α ]D 25 = −499 ( c 0.15, CH2 Cl2 ) Source of chirality: (1 R, 2 R )- trans -1, 2-cyclohexanediol and BINOL Absolute configuration: (1 R, 2 R, R a, R a ) Abstract : (1 R, 2 R )-Bis[( S )-1, 1′-binaphthyl-2, 2′-diyl]phosphitecyclohexanediol: C46 H34 O6 P2 [ α ]D 25 = +180 ( c 0.18, CH2 Cl2 ) Source of chirality: (1 R, 2 R )- trans -1, 2-cyclohexanediol and BINOL Absolute configuration: (1 R, 2 R, S a, S a ) Abstract : (1 R, 2 R )-Bis[( R )-1, 1′-H8 -binaphthyl-2, 2′-diyl]phosphitecyclohexanediol: C46 H50 O6 P2 [ α ]D 25 = −153 ( c 0.11, CH2 Cl2 ) Source of chirality: (1 R, 2 R )- trans -1, 2-cyclohexanediol and H8 -BINOL Absolute configuration: (1 R, 2 R, R a, R a ) Abstract : (1 R, 2 R )-Bis[( S )-1, 1′-H8 -binaphthyl-2, 2′-diyl]phosphitecyclohexanediol: C46 H50 O6 P2 [ α ]D 25 = +170 ( c 0.10, CH2 Cl2 ) Source of chirality: (1 R, 2 R )- trans -1, 2-cyclohexanediol and H8 -BINOL Absolute configuration: (1 R, 2 R, S a, S a )